The dynamic ups and downs of genome size evolution in Brassicaceae - Lysak, Martin A; Koch, Marcus A; Beaulieu, Jeremy M; Meister, Armin; Leitch, Ilia J (Molecular biology and evolution, 2009)
Crucifers (Brassicaceae, Cruciferae) are a large family comprising some 338 genera and c. 3,700 species. The family includes important crops as well as several model species in various fields of plant research. This paper reports new genome size (GS) data for more than 100 cruciferous species in addition to previously published C-values (the DNA amount in the unreplicated gametic nuclei) to give a data set comprising 185 Brassicaceae taxa, including all but 1 of the 25 tribes currently recognized. Evolution of GS was analyzed within a phylogenetic framework based on gene trees built from five data sets (matK, chs, adh, trnLF, and ITS). Despite the 16.2-fold variation across the family, most Brassicaceae species are characterized by very small genomes with a mean 1C-value of 0.63 pg. The ancestral genome size (ancGS) for Brassicaceae was reconstructed as (anc)1C=0.50 pg. Approximately 50% of crucifer taxa analyzed showed a decrease in GS compared with the ancGS. The remaining species showed an increase in GS although this was generally moderate, with significant increases in C-value found only in the tribes Anchonieae and Physarieae. Using statistical approaches to analyze GS, evolutionary gains or losses in GS were seen to have accumulated disproportionately faster within longer branches. However, we also found that GS has not changed substantially through time and most likely evolves passively (i.e., a tempo that cannot be distinguished between neutral evolution and weak forms of selection). The data reveal an apparent paradox between the narrow range of small GSs over long evolutionary time periods despite evidence of dynamic genomic processes that have the potential to lead to genome obesity (e.g., transposable element amplification and polyploidy). To resolve this, it is suggested that mechanisms to suppress amplification and to eliminate amplified DNA must be active in Brassicaceae although their control and mode of operation are still poorly understood.
Keywords: Phylogeny; Bayesova věta; molekulární evoluce; Evolution, Molecular; Genome, Plant; genom rostlinný; Bayes Theorem; Brassicaceae; fylogeneze